Employing popular heritage in the Iraqi theatrical actor’s performance of the play: The Thread and the Bird” as an example - Waad Abdul Amir Khalaf (Basrah Arts Journal, 2024)
In the history of Iraqi theater, popular heritage has always been a rich and abundant source of inspiration for artists. Heritage is considered an integral part of the cultural and social identity of the Iraqi people, as it carries within it values, traditions, and stories that constitute a large part of the collective consciousness. In this research, we will discuss how to employ popular heritage in the Iraqi theatrical actor’s performance of the play “The Thread and the Bird” as a model, as the actor aims to revive the heritage and present it in a way that is consistent with modern times, which helps to enhance cultural identity and connection to the roots, as popular heritage was used in the play The thread and the bird are touched in many ways, such as language, fashion, music, and dances. And motor performance. Through the above, the researcher will attempt to study this research in four chapters. The first chapter represents the methodological framework of the research problem around the following question: Was the Iraqi actor able to employ the popular heritage according to his motor and vocal tools in presenting the play The Thread and the Bird? Then the importance of the research and its goal through revealing and identifying the most important skills. The performance techniques that are compatible with the characters carrying the popular heritage in presenting the play The Thread and the Sparrow 0, then the limits of the research and definition of terminology. The second chapter, the theoretical framework, includes two sections: the first: the popular heritage (a historical view). The second section: the popular heritage and the performance of the theatrical actor, then what resulted from the theoretical framework. Of indicators, the third chapter includes procedures that include the research community, its sample, the research site, and sample analysis, then the fourth chapter includes results, conclusions, recommendations, and proposals, and the research concludes with sources Keywords: employment, popular heritage, actor’s performance.